Hibah Usaha Produktif Kreatif Dana Baznas : Studi Kasus Desa Jatisura Kecamatan Cikedung Kabupaten Indramayu - Haidar, Sumarta (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2021)
This paper is based on the results of case study research at the National Amil Zakat Agency (BAZNAS) of Indramayu Regency in Jatisura which aims to describe the implementation of BAZNAS grants in Indramayu Regency in Jatisura Village on the development program for small business capital grants and constraints in their implementation as an effort to empower the economy mustahiq. Therefore, the type of research used in this paper is field research (feld research) with an empirical approach. The data collected from the interviews and documentation are then analyzed with qualitative data analysis. There are three research results in this paper. First, BAZNAS Indramayu implemented the Small Business Capital Program to distribute zakat funds that were collected in a productive manner in the form of venture capital. The venture capital is then given back to mustahiq to start or expand the business he already has. The aim is to change the status of mustahiq to muzakki the following year. Second, the constraints experienced are lack of human resources and lack of funds collected. Third, as the government's effort to reduce poverty in the village.